CCDC68 Maintains Mitotic Checkpoint Activation by Promoting CDC20 Integration into the MCC - Qi Li; Qingzhou Chen; Tao Zheng; Fulin Wang; Junlin Teng; Haining Zhou; Jianguo Chen (Advanced Science)
Abstract The spindle assembly checkpoint (SAC) ensures chromosome segregation fidelity by manipulating unattached kinetochore‐dependent assembly of the mitotic checkpoint complex (MCC). The MCC binds to and inhibits the anaphase promoting complex/cyclosome (APC/C) to postpone mitotic exit. However, the mechanism by which unattached kinetochores mediate MCC formation is not yet fully understood. Here, it is shown that CCDC68 is an outer kinetochore protein that preferentially localizes to unattached kinetochores. Furthermore, CCDC68 interacts with the SAC factor CDC20 to inhibit its autoubiquitination and MCC disassembly. Therefore, CCDC68 restrains APC/C activation to ensure a robust SAC and allow sufficient time for chromosome alignment, thus ensuring chromosomal stability. Hence, the study reveals that CCDC68 is required for CDC20‐dependent MCC stabilization to maintain mitotic checkpoint activation.